2011
DOI: 10.1063/1.3514927
|View full text |Cite
|
Sign up to set email alerts
|

A study of the relation between translational and rotational diffusion through measurement of molecular recollision

Abstract: Translational and rotational diffusion rates of perdeuterated tempone (PDT) in ethanol are determined using electron paramagnetic resonance spectroscopy. The translational motion is measured on two scales: the macroscopic, as represented by the Heisenberg spin-exchange rate, and the microscopic, which entails recollisions between the same spin-exchange particle pair. The spin-exchange and recollision rates are used together to calculate the overall translational diffusion coefficient without recourse to assump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…The previous study in this series determined τ R for PDT in ethanol. 22 The τ R – κ T curve for ethanol generated from the data of that study lies significantly far from the alkane and aromatic curves of Figure 4, and is not shown here. It seems that the known tendency of PDT to form hydrogen bonds with ethanol 6 greatly affects the relationship between rotation and compressibility.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…The previous study in this series determined τ R for PDT in ethanol. 22 The τ R – κ T curve for ethanol generated from the data of that study lies significantly far from the alkane and aromatic curves of Figure 4, and is not shown here. It seems that the known tendency of PDT to form hydrogen bonds with ethanol 6 greatly affects the relationship between rotation and compressibility.…”
Section: Resultsmentioning
confidence: 71%
“…Previous studies 25,26 have already shown that PDT recollision forms common alkane and aromatic curves as a function of isothermal compressibility, with ethanol joining the alkanes at high temperature. 22 Figure 4 shows τ R as a function of κ T in all solvents (see Refs. 25 and 26 and references therein for details on how compressibilities were obtained).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, even in this case, it is possible to distinguish the significantly different contributions of dipole-dipole interaction and spin exchange to broadening of the spectral lines by means of the method [12]. Recently it was supposed [20][21][22] that paramagnetic molecules in the solvent cage repeatedly collide and exchange their spin states. In such case the spin exchange does not reflect adequately the rate of translational diffusion of molecules in the medium.…”
Section: Determination Of the Translation Diffusion Coefficients Of Tmentioning
confidence: 99%